Searching for Active Factors in Diverse Approaches to Psychotherapy – Types of Intervention and Temporal Aspects: Brief Research Report - Koemeda-Lutz, Margit; Crameri, Aureliano; Schulthess, Peter; Wyl, Agnes von; Tschuschke, Volker (Bioenergetic Analysis, 2016)
This paper is a synopsis of scientific research on treatment effectiveness of ten varying approaches to psychotherapy. Different types of psychotherapy justify their existence by the basic assumption that therapeutic change is effectuated by specific concepts, attitudes and interventional techniques. In comparative psychotherapy research, for many years, studies have quantified outcome differences (see e.g. Lambert, 2013), and only very few have closely examined the process of treatment. The study reported here was part of a larger multi-center naturalistic process-outcome study (pre-post-follow-up, see e.g. von Wyl et al., 2013; Crameri et al., 2015; Tschuschke et al., 2015), named PAP-S, which included 362 patients from 81 therapists. The synopsis includes methods as well as results and discussion.